Preconditioning with rHMGB1 ameliorates lung ischemia–reperfusion injury by inhibiting alveolar macrophage pyroptosis via the Keap1/Nrf2/HO-1 signaling pathway - Lin Fei; Xiao Jingyuan; Liang Fangte; Dai Huijun; Ye Liu; Jing Ren; Lin Jinyuan; Pan Linghui (Journal of Translational Medicine, 2020)
Abstract Background Lung ischemia–reperfusion injury (LIRI) is a complex pathophysiological process that can lead to poor patient outcomes. Inflammasome-dependent macrophage pyroptosis contributes to organ damage caused by ischemia/reperfusion injury. Oxidative stress and antioxidant enzymes also play an important role in LIRI. In this study, we conducted experiments to investigate whether and how preconditioning with rHMGB1 could ameliorate LIRI in a mouse model. Methods Adult male BALB/c mice were anesthetized, the left hilus pulmonis was clamped, and reperfusion was performed. rHMGB1 was administered via intraperitoneal injection before anesthesia, and brusatol was given intraperitoneally every other day before surgery. We measured pathohistological lung tissue damage, wet/dry mass ratios of pulmonary tissue, and levels of inflammatory mediators to assess the extent of lung injury. Alveolar macrophage pyroptosis was evaluated by measuring release of lactate dehydrogenase, caspase-1 expression was assessed using flow cytometry, and gasdermin-D expression was analyzed using immunofluorescent staining. Levels of oxidative stress markers and antioxidant enzymes were also analyzed. Results Preconditioning with rHMGB1 significantly ameliorated lung injury induced by ischemia–reperfusion, based on measurements of morphology, wet/dry mass ratios, as well as expression of IL-1β, IL-6, NF-κB, and HMGB1 in lung tissues. It also alleviated alveolar macrophage pyroptosis, reduced oxidative stress and restored the activity of antioxidant enzymes. These beneficial effects were mediated at least in part by the Keap1/Nrf2/HO-1 pathway, since they were reversed by the pathway inhibitor brusatol. Conclusions Preconditioning with rHMGB1 may protect against LIRI by suppressing alveolar macrophage pyroptosis. This appears to involve reduction of oxidative stress and promotion of antioxidant enzyme activity via the Keap1/Nrf2/HO-1 pathway.